Electroacupuncture-Induced Plasticity between Different Representations in Human Motor Cortex - Weiqin Peng; Tiange Yang; Jiawei Yuan; Jianpeng Huang; Jianhua Liu (Neural Plasticity)
Somatosensory stimulation can effectively induce plasticity in the motor cortex representation of the stimulated body part. Specific interactions have been reported between different representations within the primary motor cortex. However, studies evaluating somatosensory stimulation-induced plasticity between different representations within the primary motor cortex are sparse. The purpose of this study was to investigate the effect of somatosensory stimulation on the modulation of plasticity between different representations within the primary motor cortex. Twelve healthy volunteers received both electroacupuncture (EA) and sham EA at the TE5 acupoint (located on the forearm). Plasticity changes in different representations, including the map volume, map area, and centre of gravity (COG) were evaluated by transcranial magnetic stimulation (TMS) before and after the intervention. EA significantly increased the map volume of the forearm and hand representations compared to those of sham EA and significantly reduced the map volume of the face representation compared to that before EA. No significant change was found in the map volume of the upper arm and leg representations after EA, and likewise, no significant changes in map area and COG were observed. These results suggest that EA functions as a form of somatosensory stimulation to effectively induce plasticity between different representations within the primary motor cortex, which may be related to the extensive horizontal intrinsic connectivity between different representations. The cortical plasticity induced by somatosensory stimulation might be purposefully used to modulate human cortical function.